Ectopic Lymphoid Follicle Formation and Human Seasonal Influenza Vaccination Responses Recapitulated in an Organ‐on‐a‐Chip (Adv. Sci. 14/2022). Issue 14 (16th May 2022) - Goyal, Girija; Prabhala, Pranav; Mahajan, Gautam; Bausk, Bruce; Gilboa, Tal; Xie, Liangxia; Zhai, Yunhao; Lazarovits, Roey; Mansour, Adam; Kim, Min Sun; Patil, Aditya; Curran, Danielle; et al.
Abstract : Organ‐on‐a‐Chip A microfluidic organ‐on‐a‐chip model of the human lymphoid follicle that recapitulates vaccination responses in vitro. Blood‐derived cells self assemble into germinal centers in a matrix gel in the lower channel when nutrient medium is flowed through the upper channel. Antigen‐specific antibodies and cytokines are secreted in response to seasonal influenza vaccination that mirror responses observed in patients. More details can be found in article number 2103241 by Donald E. Ingber and co‐workers.